2006
DOI: 10.1158/1078-0432.ccr-05-2861
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Lineage Leukemia–Rearranged Childhood Pro-B and CD10-Negative Pre-B Acute Lymphoblastic Leukemia Constitute a Distinct Clinical Entity

Abstract: Purpose: Mixed lineage leukemia (MLL) abnormalities occur in f50% of childhood pro-B acute lymphoblastic leukemia (ALL). However, the incidence and type of MLL rearrangements have not been determined in common ALL (cALL) and CD10+ or CD10À pre-B ALL. Experimental Design: To address this question, we analyzed 29 patients with pro-B ALL, 11patients with CD10À pre-B ALL, 23 pre-B, and 26 cALL patients with CD10 on 20% to 80%, as well as 136 pre-B and 143 cALL patients with CD10 z80% of blasts. They were all enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 39 publications
3
27
0
1
Order By: Relevance
“…Furthermore, in 2 out of 30 MLL-positive cases analyzed by GS methods, the rearrangement was found in CD10( þ ) samples: one in a patient with CALL and one in a patient with pre-B ALL. While Attarbaschi et al 8 question the use of NG2 as a marker for MLL rearranged BPC-ALL, we point out that NG2 expression, evaluated by a combination of qualitative and quantitative FC analysis, is a highly reliable marker for MLL diagnosis, more than the absence of CD10. By collecting immunophenotypic NG2 data from 1461 B-ALL patients using both qualitative and quantitative methods, we tested FC performances according to GS response: sensitivity, specificity, predictive values and accuracy for both approaches produced comparable results with no significant differences in MLL diagnosis.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Furthermore, in 2 out of 30 MLL-positive cases analyzed by GS methods, the rearrangement was found in CD10( þ ) samples: one in a patient with CALL and one in a patient with pre-B ALL. While Attarbaschi et al 8 question the use of NG2 as a marker for MLL rearranged BPC-ALL, we point out that NG2 expression, evaluated by a combination of qualitative and quantitative FC analysis, is a highly reliable marker for MLL diagnosis, more than the absence of CD10. By collecting immunophenotypic NG2 data from 1461 B-ALL patients using both qualitative and quantitative methods, we tested FC performances according to GS response: sensitivity, specificity, predictive values and accuracy for both approaches produced comparable results with no significant differences in MLL diagnosis.…”
mentioning
confidence: 60%
“…2,[5][6][7] Attarbaschi et al 8 recently published a study, on behalf of the BFM cooperative study group, in which they report absolute sensitivity and 0.78 specificity for absence of CD10 expression (CD10À) in pro-B and pre-B ALL as phenotypic marker for predicting MLL rearrangements. Our results show that the absence of CD10 in BP-ALL patients with MLL rearrangements has very low specificity (28/86, 32.56%), while the presence of NG2 accounts for high sensitivity (87-90%) and specificity (99-100%).…”
mentioning
confidence: 99%
“…This finding is supported by recent studies suggesting that CD10-negative pre-B-ALL cases may represent pro-B-ALL cases that maintain their tendency to rearrange and express their Ig heavy chain. 50,51 A recent study suggested that MLL-AF4-positive infant ALL is initiated later in fetal development than most MLL-AF4-negative childhood B-cell precursor ALL (o3 years), based on the presence and absence of nucleotide insertions at the DH-JH junction, respectively. 22 In line with this observation, nucleotide insertion at the DH-JH junction was present in 73% of MLL-AF4 infant ALL cases in this study.…”
Section: Discussionmentioning
confidence: 99%
“…13 The detection of MLL rearrangements was preferentially based on reverse transcription polymerase chain reaction or MLL split-signal fluorescence in situ hybridization analysis. 2,14 However, classic 11q23 translocations without reverse transcription polymerase chain reaction/ fluorescence in situ hybridization confirmation also counted for MLL ϩ cases. Patients were treated with informed consent from the patient's parents or legal guardians.…”
Section: Patientsmentioning
confidence: 99%